Interfaces of Molecular Recognition Sites and Biosensors; Novel Bio-Sensing Materials. Issue 1793 (9th June 2015) - Choi, Kyung M.
ABSTRACT: We introduce a sensing element, "Molecularly Imprinted Polymer (MIP), " which created by "Molecular Imprinted Technique." However, the sensitivity of MIP's based bio-sensors limits for practical applications due to the low sensitivity. To achieve a high sensitivity of MIP's based sensors, the synthesis of "high affinity receptor or binding sites, " such as "monoclonal particles" is a key objective. In previous studies, affinity distribution plots indicated that "high affinity binding sites" were obtained when the number of binding sites per particle decreased. It means that smaller particles are expected to have higher affinity binding sites compared to larger particles. The result motivated us to produce small-sized MIP's particles for the achievement of higher sensitivity. Microfluidic Synthesis has taken a great attention to synthesize small particles. However, the microfluidic synthesis gave us a difficulty, especially collections of MIP's particles from the surface of PDMS-based microchannels due to a sticking problem. Thus, we employed a new approach, which can collect MIP's particles without any sticking problem from the surface of the reactor. It is a photopatterned MIP's system generated on the glass surface. We prepared a photomask with micro-sized patterns and then fabricate MIP's particles on a glass surface by photopolymerization. Uniform MIP's patterns were printed on the glass surface. The interface between the glass surface and the MIP's pattern was observed by SEM. Micro-sized MIP's particles were collected from the glass surface by scratching off the photocured MIP's patterns.